2015
DOI: 10.1111/acer.12747
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Delivered Screening and Brief Intervention for Alcohol Use in Pregnancy: A Pilot Randomized Trial

Abstract: Background Although screening and brief intervention (SBI) for unhealthy alcohol use has demonstrated efficacy in some trials, its implementation has been limited. Technology-delivered approaches are a promising alternative, particularly during pregnancy when the importance of alcohol use is amplified. The present trial evaluated the feasibility and acceptability of an interactive, empathic, video-enhanced, and computer-delivered SBI (e-SBI) plus three separate tailored mailings, and estimated intervention eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(111 citation statements)
references
References 48 publications
1
106
0
4
Order By: Relevance
“…Several studies reported on the acceptability of their interventions to participants and generally reported positive to very positive ratings. 79,97,116,117,130 Findings in the current review were generally consistent with the findings of the previous USPSTF review. 176 For test accuracy, the previous reviewers concluded that a single-question screener, the AUDIT-C, and the AUDIT appeared to be the best overall instruments for screening adults for the full spectrum of unhealthy alcohol use in primary care, with ranges of sensitivities and specificities solidly in the range of the sensitivities and specificities seen in this review among studies of adults.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies reported on the acceptability of their interventions to participants and generally reported positive to very positive ratings. 79,97,116,117,130 Findings in the current review were generally consistent with the findings of the previous USPSTF review. 176 For test accuracy, the previous reviewers concluded that a single-question screener, the AUDIT-C, and the AUDIT appeared to be the best overall instruments for screening adults for the full spectrum of unhealthy alcohol use in primary care, with ranges of sensitivities and specificities solidly in the range of the sensitivities and specificities seen in this review among studies of adults.…”
Section: Discussionsupporting
confidence: 88%
“…Studies show that the majority of women reduce their drinking levels during pregnancy [26], but a substantial percentage return to pre-pregnancy levels after having given birth [27]. Few studies have been conducted applying digital BIs to reduce drinking during pregnancy [28,29]; however, postpartum drinking has received limited attention so far. Ondersma et al [30] evaluated the effect of a computer-based BI on 7-day point-prevalence abstinence and drinking days among postpartum women.…”
Section: Brief Interventionsmentioning
confidence: 99%
“…Research into technology-delivered interventions has grown rapidly in recent years, with meta-analyses showing encouraging evidence for efficacy with respect to substance abuse [1822] as well as other health-related behaviours [23]. However, although some early studies have considered e-SBI for alcohol use during pregnancy [24,25], none have done so for postpartum drinking.…”
Section: Introductionmentioning
confidence: 99%
“…The e-SBI session for this study was built and delivered using a flexible e-intervention authoring platform that has been used in a number of related trials [2529], which uses a Tablet PC to deliver screening, assessment, and intervention content as a web application (see intervention section, below, for further details). We hypothesised that women receiving the e-SBI would report higher 7-day point-prevalence abstinence from alcohol and fewer days of alcohol use.…”
Section: Introductionmentioning
confidence: 99%